The age difference in 2D:4D among the Polish population: An exploratory study - Pruszkowska-Przybylska, Paulina; Kobus, Magdalena; Żądzińska, Elżbieta; Rosset, Iwona; Pruszkowska, Milena; Kuczyński, Wojciech; Sitek, Aneta (Anthropological Review, 2023)
In this study a widely debated association between 2D:4D digit ratio and age was investigated. The study material included 960 individuals (530 females and 430 males) from Central Poland aged between 6–79 years. The information about age was obtained via survey filled in by study participants or, if underaged, their parents. The direct measurements of the second and fourth finger were performed to assess the 2D:4D digit ratio. The 2D:4D digit ratios for the left hand were significantly correlated with age both among females and males. In women the 2D:4D digit ratios for the right hand were significantly correlated with age. There were also significant differences in digit ratio between age groups. The results of our study suggest that there might be an association between digit ratio and age, and the direction of the correlation might be related to the phase of the ontogenesis.